2021
DOI: 10.1002/jee.20393
|View full text |Cite
|
Sign up to set email alerts
|

Using random forest analysis to identify student demographic and high school‐level factors that predict college engineering major choice

Abstract: Background Given the importance of engineers to a nation's economy and potential innovation, it is imperative to encourage more students to consider engineering as a college major. Previous studies have identified a broad range of high school experiences and demographic factors associated with engineering major choice; however, these factors have rarely been ranked or ordered by relative importance. Purpose/Hypothesis This study leveraged comprehensive, longitudinal data to identify which high school‐level fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 74 publications
6
23
0
Order By: Relevance
“…Importantly, this perspective facilitates the understanding of how factors related to individual backgrounds, social networks, institutional academic programs, organizations, and the environment intersect in important ways to generate trends in engineering major participation. Using the life course perspective enables us to comprehensively illustrate how factors across different life stages are associated with engineering major choice, in line with other research showing the interconnectedness between K-12 and postsecondary education in helping encourage greater and more diverse participation in engineering (e.g., Tan et al, 2021).…”
Section: Conceptual Framework: Life Course Perspectivesupporting
confidence: 59%
See 4 more Smart Citations
“…Importantly, this perspective facilitates the understanding of how factors related to individual backgrounds, social networks, institutional academic programs, organizations, and the environment intersect in important ways to generate trends in engineering major participation. Using the life course perspective enables us to comprehensively illustrate how factors across different life stages are associated with engineering major choice, in line with other research showing the interconnectedness between K-12 and postsecondary education in helping encourage greater and more diverse participation in engineering (e.g., Tan et al, 2021).…”
Section: Conceptual Framework: Life Course Perspectivesupporting
confidence: 59%
“…Previous studies have identified a wide range of factors that are associated with student major choice. In general, these factors can be organized into three main categories: individual characteristics and factors, social influences, and structural factors (e.g., Adelman, 1998;Blickenstaff, 2005;Cruz & Kellam, 2018;Darolia et al, 2020;Griffith & Main, 2021;Johnson & Sheppard, 2004;Lent et al, 2008;Main et al, 2015;Main, Darolia, et al, 2017;Main & Ost, 2011, 2014Main, Tan, et al, 2020;Main, Xu, et al, 2017;Marra et al, 2012;Matusovich et al, 2010;Ong et al, 2011;Seymour & Hewitt, 1997;Tan et al, 2021;Tonso, 1999Tonso, , 2006Tsui, 2010). Individual characteristics can include student demographic characteristics, academic achievement, motivation, and identity, whereas structural factors can include high school characteristics, high school geographical location, and the availability of math and science courses.…”
Section: Factors Influencing College Major Choicementioning
confidence: 99%
See 3 more Smart Citations